Indirect measure of visceral adiposity 'A Body Shape Index' (ABSI) is associated with arterial stiffness in patients with type 2 diabetes. Issue 1 (18th March 2016) - Bouchi, Ryotaro; Asakawa, Masahiro; Ohara, Norihiko; Nakano, Yujiro; Takeuchi, Takato; Murakami, Masanori; Sasahara, Yuriko; Numasawa, Mitsuyuki; Minami, Isao; Izumiyama, Hajime; Hashimoto, Koshi; Yoshimoto, Takanobu; et al.
Abstract : Objective: Among indirect measures of visceral adiposity, A Body Shape Index (ABSI), which is defined as waist circumference (WC)/(body mass index (BMI) 2/3 ×height 1/2 ), is unique in that ABSI is positively correlated with visceral adiposity and is supposed to be independent of BMI. ABSI has been also shown to be linearly and positively associated with visceral fat mass and all-cause and cardiovascular disease (CVD) in the general population. It is, however, uncertain whether ABSI could be associated with arterial stiffness in patients with diabetes. Methods: This is a cross-sectional study of 607 patients with type 2 diabetes (mean age 64±12 years; 40.0% female). Visceral fat area (VFA, cm 2 ) and subcutaneous fat area (SFA, cm 2 ) were assessed with a dual-impedance analyzer. In order to estimate the risk for CVD, brachial-ankle pulse wave velocity (baPWV, cm) was used for the assessment of arterial stiffness. Results: ABSI was significantly and positively correlated with VFA (r=0.138, p=0.001) and negatively associated with BMI (r=−0.085, p=0.037). The correlation of z-score for ABSI with VFA remained significant (r=0.170, p<0.001) but not with BMI (r=0.009, p=0.820). ABSI (standardized β 0.095, p=0.043) but not WC (standardized β −0.060, p=0.200) was significantly and positively correlated with baPWV in the multivariate model including BMI as a covariate. Conclusions: ABSI appears to reflect visceral adiposity independently of BMI and to be a substantial marker of arterial stiffening in patients with type 2 diabetes.